Engyprosopon keliaoense, a new lefteye flounder (Teleostei: Bothidae) from Taiwan - Amaoka, Kunio; Ho, Hsuan-Ching (Zootaxa, 2022)
A new bothid flounder, Engyprosopon keliaoense sp. nov., is described on the basis of 4 specimens collected from off southwestern Taiwan. The new species belongs to these congeners with a pair of black botches on the caudal fin and is most similar to E. grandisquama (Temminck & Schlegel). It can be separated from the latter by having smaller upper and lower eyes, narrower interorbital width, shorter pectoral fin on the ocular side, and more scales in the lateral line. Investigation on Rhombus grandisquama and its junior synonyms revealed that Rhombodoichthys spilurus Günther and Rhombus poecilurus Bleeker are retained as junior synonyms of E. grandisquama, whereas Rhombodoichthys spiniceps Macleay and Scaeops orbicularis Jordan & Seale are now excluded from the synonymy of E. grandisquama.